2020
DOI: 10.1371/journal.ppat.1008599
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 in protozoan infections: A tale of resistance and disease tolerance

Abstract: Heme oxygenase (HO-1) mediates the enzymatic cleavage of heme, a molecule with proinflammatory and prooxidant properties. HO-1 activity deeply impacts host capacity to tolerate infection through reduction of tissue damage or affecting resistance, the ability of the host to control pathogen loads. In this Review, we will discuss the contribution of HO-1 in different and complex protozoan infections, such as malaria, leishmaniasis, Chagas disease, and toxoplasmosis. The complexity of these infections and the ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 126 publications
(167 reference statements)
0
18
0
Order By: Relevance
“…The role of heme-induced oxidative stress in malaria pathogenesis has been validated in different in vivo studies using knockout mice lacking the gene for HO-1. HO-1 breaks down heme into biliverdin and carbon monoxide (CO), which are antioxidants ( Silva et al, 2020 ), and iron, which can be bound by the iron-binding protein ferritin ( Balla et al, 2005 ). Expression of HO-1 in the context of Plasmodium infection is important in the prevention of cerebral malaria in mice ( Pamplona et al, 2007 ).…”
Section: Oxidative Stress and The Pathogenesis Of Malariamentioning
confidence: 99%
“…The role of heme-induced oxidative stress in malaria pathogenesis has been validated in different in vivo studies using knockout mice lacking the gene for HO-1. HO-1 breaks down heme into biliverdin and carbon monoxide (CO), which are antioxidants ( Silva et al, 2020 ), and iron, which can be bound by the iron-binding protein ferritin ( Balla et al, 2005 ). Expression of HO-1 in the context of Plasmodium infection is important in the prevention of cerebral malaria in mice ( Pamplona et al, 2007 ).…”
Section: Oxidative Stress and The Pathogenesis Of Malariamentioning
confidence: 99%
“…Here, we discuss the effects, after noninfectious insults, of HO-1 expression in different organs of the body. Although, HO-1 expression has already been shown to exert protection against infectious insults in many organs, in this latter case, the specific pathogen under discussion will have major impacts on HO-1 role as a host protective mechanism, since HO-1 expression might impact on pathogen burden as well [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The chronicity of the disease with diverse parasites suggests the development of an immunosuppressive process during the infection [ 143 ]. Notably, it was shown that the activity of HO-1 could interfere with the resistance process, both by the elimination of heme and by the products of this enzymatic reaction [ 144 ]. Thus, the induction of HO-1, on the one hand, impairs phagocytosis and, on the other, reduces the secretion of pro-inflammatory cytokines [ 143 ].…”
Section: Therapeutic Implications Of Ho Inhibitorsmentioning
confidence: 99%